2022
DOI: 10.17762/ijcnis.v14i3.5601
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Cloud Service Providers in Improving Resource Allocation and Data Integrity by 4G IoT Paradigm

Abstract: Due to the expansion of Internet of Things (IoT), the extensive wireless, and 4G networks, the rising demands for computing calls and data communication for the emergent EC (EC) model. By stirring the functions and services positioned in the cloud to the user proximity, EC could offer robust transmission, networking, storage, and transmission capability. The resource scheduling in EC, which is crucial to the accomplishment of EC system, has gained considerable attention. This manuscript introduces a new lighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Tentatively, ADLI was first attempted in the principal paper of Kaushik et al (2013), in which they repeated improvement circumstances differentiating an item drove (for the most part, manufacturing drove) industrialization framework and ADLI, for South Korea in 1963. They found that while the two methods would make improvement, ADLI would provoke better as a rule stood out from exchange drove advancement, as ADLI incited higher work maintenance, more comparable spread of pay, less dejection, and a higher speed of per capita economic advancement (Bhatt et al, 2022).…”
Section: Figure 3 Economic Growth Due To Agriculture Classificationmentioning
confidence: 99%
“…Tentatively, ADLI was first attempted in the principal paper of Kaushik et al (2013), in which they repeated improvement circumstances differentiating an item drove (for the most part, manufacturing drove) industrialization framework and ADLI, for South Korea in 1963. They found that while the two methods would make improvement, ADLI would provoke better as a rule stood out from exchange drove advancement, as ADLI incited higher work maintenance, more comparable spread of pay, less dejection, and a higher speed of per capita economic advancement (Bhatt et al, 2022).…”
Section: Figure 3 Economic Growth Due To Agriculture Classificationmentioning
confidence: 99%